2021
DOI: 10.1016/j.sjbs.2020.11.082
|View full text |Cite
|
Sign up to set email alerts
|

Combined in vitro and in silico approach to evaluate the inhibitory potential of an underutilized allium vegetable and its pharmacologically active compounds on multidrug resistant Candida species

Abstract: Candida infections and related mortality have become a challenge to global health. Nontoxic and natural bioactive compounds from plants are regarded as promising candidates to inhibit these multidrug resistant strains. In the present study, in vitro assays and in silico molecular docking approach was combined to evaluate the inhibitory effect of crude extracts from Allium ampeloprasum and its variety A. porrum on Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The distance produced by the presence of hydrogen bonds ranges from 2.11684 - 3.21115 Å, while the hydrophobic interaction has a distance of 4.60759 Å. Liberato et al 35 through an in vitro study, explained that gallic acid has potential as antifungal activity against Candida spp. Another study also reported, through in vitro and in silico studies by Uma Maheshwari Nallal et al 30 , that gallic acid, which is classified as an active phytochemical compound, is predicted to be an effective inhibitory agent of Sap from Candida species. Therefore, even though in this research gallic acid did not interact with the substrate binding site pocket or the catalytic residue of the target receptor, gallic acid was predicted to have a reasonably good interaction in inhibiting Sap 3.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The distance produced by the presence of hydrogen bonds ranges from 2.11684 - 3.21115 Å, while the hydrophobic interaction has a distance of 4.60759 Å. Liberato et al 35 through an in vitro study, explained that gallic acid has potential as antifungal activity against Candida spp. Another study also reported, through in vitro and in silico studies by Uma Maheshwari Nallal et al 30 , that gallic acid, which is classified as an active phytochemical compound, is predicted to be an effective inhibitory agent of Sap from Candida species. Therefore, even though in this research gallic acid did not interact with the substrate binding site pocket or the catalytic residue of the target receptor, gallic acid was predicted to have a reasonably good interaction in inhibiting Sap 3.…”
Section: Resultsmentioning
confidence: 92%
“…The test ligands that have binding energy close to pepstatin are turgorin with a binding energy of 7,480 kcal/mol and K d 3289177.500 pM, then based on the binding energy respectively, D-glucuronic acid with a binding energy of 6.219 kcal/mol and Kd 27632016.000 pM, gallic acid with a binding energy of 6.053 kcal/mol and Kd 36567240.000 pM, L-norepinephrine with a binding energy of 5.770 kcal/mol and Kd 58956804.000 pM, mimosine with a binding energy of 5.599 kcal/mol and Kd 78682576.000 pM, L-ascorbic acid with a binding energy of 5.390 kcal/mol and Kd 111963792.000 pM, and the lowest binding energy is linolenic acid with a binding energy of 5.168 kcal/mol and Kd 162856752.000. The more positive value of the binding energy indicates stronger bond between the ligand and the target receptor whereas 29,30 . The results of the binding energies are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is another hydrogen bond acceptor between the amino acid Lys89 and the carbonyl of the indolin-2-one ring. The role of hydrogen bonds in establishing out the ligand binding specificity [64,65], and its significance for biomacromolecules' properties and structures has been defined theoretically and experimentally [64]. The results indicated that the comparable positions and orientations within the investigated ligands assumed the binding site of the target enzyme.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Azoles (itraconazole and voriconazole) and polyenes (amphotericin B) are antifungals that have widely been used to control invasive human fungal infections for more than 4 decades ( Jørgensen and Heick, 2021 ; Uma Maheshwari Nallal et al, 2021 ). The clinical use of azoles is of high priority since there are only a few available alternatives for prophylactic and therapeutic treatment of C. lunata infections ( Chowdhary et al, 2014 ; Chang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%